Applying the Zachman Framework to Enterprise Architecture in E Commerce Retail Services - Marnoto (Global Research and Collaboration, 2025)
Zachman Framework is an architectural framework used to analyze and organize the various perspectives involved in a system. In the context of AliExpress's retail services, the application of the Zachman Framework can provide a comprehensive understanding of the system, facilitate coordination between business entities, increase operational efficiency, promote continuous development and innovation, and assist in better risk management. In implementing it on AliExpress, the Zachman Framework helps in understanding the business entities involved, such as suppliers, customers, deliveries, and sellers, and identifying their roles and interactions. Through in-depth analysis, this framework enables AliExpress to better coordinate business activities, increase synergies, and reduce bottlenecks. In addition, the Zachman Framework also allows AliExpress to analyze and understand their operational processes from various perspectives, such as business, technology, and data perspectives. With a better understanding of their systems, AliExpress can identify areas where operational efficiency can be improved, optimize processes and increase productivity.